Perception of Law 1761/2015 and the Context of Femicides (2017)
Introduction: This research contextualizes the cases of femicide that occurred in Cali, Valle del Cauca, Colombia during the 2015-2016 period, identifies the procedural stage, and allows to know the perception and intersectoral actions taken by the institutions responsible for accomplishing the objectives of Law 1761/2015. Materials and methods: A cross-sectional descriptive study was conducted, doing an exhaustive individual survey of officials of the National Institute of Legal Medicine and Forensic Sciences, the National Prosecutor General’s Office, the National Police and the Ombudsman’s Office, who intervene in solving this crime. Subsequently, data from all the cases classified as femicide in the 2015-2016 period was collected. Results and discussion: One of the most significant findings was that women who were single, had a domestic partnership or did not receive basic education were the most affected. Femicides occurred mainly to the east of the city (Aguablanca District). Most were committed by individuals who were very close to the victims. When the death of the woman occurred after the medical-legal assessment, prosecution of the murderers was achieved. Conclusions: The study concluded that the population needs to be educated and made aware of the prevention of gender violence. In addition, at the inter-institutional level, conceptualization and theory must be reinforced to approach and punish crime.